2019
DOI: 10.3389/fonc.2019.00890
|View full text |Cite
|
Sign up to set email alerts
|

The Highly Pure Neem Leaf Extract, SCNE, Inhibits Tumorigenesis in Oral Squamous Cell Carcinoma via Disruption of Pro-tumor Inflammatory Cytokines and Cell Signaling

Abstract: Oral squamous cell carcinoma (OSCC) is a deadly disease that comprises 60% of all head and neck squamous cell cancers. The leaves of the Neem tree (Azadirachta indica) have been used in traditional Ayurvedic medicine for centuries to treat numerous oral maladies and are known to have significant anti-inflammatory properties. We hypothesize that a highly pure super critical CO2 Neem leaf extract (SCNE) prevents initiation and progression of OSCC via downregulation of intra-tumor pro-inflammatory pathways, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 54 publications
1
36
1
Order By: Relevance
“…Though no studies have investigated the effect of neem extract on systemic inflammatory markers in diabetic humans, several studies have reported that neem extract can reduce the levels of pro-inflammatory cytokines (IL-6 and TNF-α) in experimentally-inflammation-induced laboratory animals, which supports our findings. [39][40][41][42][43] It is promising to note that most of the outcome measures in the present study are also significant at 8 weeks as well as 4 weeks of treatment with NEEM, compared to the placebo.…”
Section: Discussionmentioning
confidence: 50%
“…Though no studies have investigated the effect of neem extract on systemic inflammatory markers in diabetic humans, several studies have reported that neem extract can reduce the levels of pro-inflammatory cytokines (IL-6 and TNF-α) in experimentally-inflammation-induced laboratory animals, which supports our findings. [39][40][41][42][43] It is promising to note that most of the outcome measures in the present study are also significant at 8 weeks as well as 4 weeks of treatment with NEEM, compared to the placebo.…”
Section: Discussionmentioning
confidence: 50%
“…On analysing the various models for research on oral squamous cell carcinoma it was found that animal models were used for 10 research articles [3][4][5][6][7][8][9][10][11][12] venous blood from patients with histopathologically confirmed OSCC was used in 2 research articles 13,14 and OSCC cell lines were utilized in 4 research articles. 11,12,14,15 Different parts of the neem plant have been implicated as a cure for many ailments. Neem leaf extracts, neem leaf glycoproteins and liminoids have been the mainstay of research for their anticancer properties in OSCC.…”
Section: Resultsmentioning
confidence: 99%
“…10 Morris J et al (2019) demonstrated that a highly pure neem leaf extract effectively decreased the pro-cancer inflammatory cytokines and caused disruption of cell signaling and cell migration. 11 Neem leaf glycoprotein has also been shown to improve the migratory capability of monocytes and augment the cytotoxic potential of T lymphocytes. 14 Super critical CO2 neem leaf extract (SCNE) and its bioactive compound, NIM have been shown to decrease the various pro tumour inflammatory mediators and also simultaneously modify cellular signalling in OSCC cell lines.…”
Section: Other Anticancer Mechanisms Of Neem Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In oral squamous cell carcinoma (OSCC) animal models, highly pure super critical CO 2 leaf extract of Azadirachta indica (Neem) induces an M1 phenotype in TAMs in vivo, and the primary active component, nimbolide (a limonoid tetranortriterpenoid with an α,β-unsaturated ketone system and a δ-lactone ring) has significant anticancer activity in established OSCC xenografts [90]. β-Elemene, a widely known sesquiterpene, regulated the polarization of macrophages from M2 to M1, inhibiting the proliferation, migration and invasion of lung cancer cells and enhancing its radiosensitivity [91].…”
Section: Other Herbal Compounds/preparationsmentioning
confidence: 99%